Antrodia camphorata Mycelia Exert Anti-liver Cancer Effects and Inhibit STAT3 Signaling in vitro and in vivo - Zhu, Pei-Li; Fu, Xiu-Qiong; Li, Jun-Kui; Tse, Anfernee Kai-Wing; Guo, Hui; Yin, Cheng-Le; Chou, Ji-Yao; Wang, Ya-Ping; Liu, Yu-Xi; Chen, Ying-Jie; Hossen, Muhammad Jahangir; Zhang, Yi; et al. (Frontiers in Pharmacology, 2018)
Hepatocellular carcinoma (HCC), the major form of primary liver cancer, is a common cause of cancer-related death worldwide. Signal transducer and activator of transcription 3 (STAT3) signaling is constantly activated in HCC and has been proposed as a chemotherapeutic target for HCC. Antrodia camphorata (AC), a medicinal mushroom unique to Taiwan, is traditionally used for treating HCC. Whereas natural AC is scarce, cultured AC mycelia are becoming alternatives. In this study, we investigated the anti-HCC effects of the ethyl acetate fraction of an ethanolic extract of AC mycelia (EEAC), particularly exploring the involvement of STAT3 signaling in these effects. We found that EEAC reduced cell viability, induced apoptosis, and retarded migration and invasion in cultured HepG2 and SMMC-7721 cells. Immunoblotting results showed that EEAC downregulated protein levels of phosphorylated and total STAT3 and JAK2 (an upstream kinase of STAT3) in HCC cells. Real-time PCR analyses showed that STAT3, but not JAK2, mRNA levels were decreased by EEAC. EEAC also lowered the protein level of nuclear STAT3, decreased the transcriptional activity of STAT3, and downregulated protein levels of STAT3-targeted molecules, including anti-apoptotic proteins Bcl-xL and Bcl-2, and invasion-related proteins MMP-2 and MMP-9. Over-activation of STAT3 in HCC cells diminished the cytotoxic effects of EEAC. In SMMC-7721 cell-bearing mice, EEAC (100 mg/kg, i.g. for 18 days) significantly inhibited tumor growth. Consistent with our in vitro data, EEAC induced apoptosis and suppressed JAK2/STAT3 activation/phosphorylation in the tumors. Taken together, EEAC exerts anti-HCC effects both in vitro and in vivo; and inhibition of STAT3 signaling is, at least in part, responsible for these effects. We did not observe significant toxicity of EEAC in normal human liver-derived cells, nude mice and rats. Our results provide a pharmacological basis for developing EEAC as a safe and effective agent for HCC management.